Ultralow power continuous-wave frequency conversion in hydrogenated amorphous silicon waveguides - Wang, Ke-Yao; Foster, Amy C (Optics letters, 2012)
We demonstrate wavelength conversion through nonlinear parametric processes in hydrogenated amorphous silicon (a-Si:H) with maximum conversion efficiency of -13 dB at telecommunication data rates (10 GHz) using only 15 mW of pump peak power. Conversion bandwidths as large as 150 nm (20 THz) are measured in continuous-wave regime at telecommunication wavelengths. The nonlinear refractive index of the material is determined by four-wave mixing (FWM) to be n(2)=7.43×10(-13) cm(2)/W, approximately an order of magnitude larger than that of single crystal silicon.